Komunikasi Efektif Sebagai Metode Utama dalam Pengabdian Masyarakat untuk Peningkatan Baca Siswa SMK Swasta - Dani Fadillah; Muthi'muzayanah Selmia Fitri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the main role of effective communication in the success of community service at SMK Perindustrian Yogyakarta. The research method used is qualitative with an Effective Communication approach, involving in-depth interviews with various stakeholders in schools with the main focus on the success of effective communication with students. The discovery of a lack of interest in reading in schools is the main focus of this study to improve reading behavior in assigned schools. The results of the study indicate that effective communication plays an important role in facilitating various stages of work program implementation. Good communication allows messages to be conveyed in accordance with the objectives of the successful implementation of the Kampus Mengajar 7 work program which was implemented for 4 months. The active involvement of all parties in the communication process has helped coordination between units at SMKS Perindustrian Yogyakarta. This greatly minimizes administrative and technical obstacles that may arise in its implementation. This study concludes that effective communication is the most important key factor supporting the success of community service in the implementation of the Kampus Mengajar 7 work program at SMKS Perindustrian Yogyakarta. Recommendations for further research include increasing communication capacity between all stakeholders and implementing information technology to facilitate more efficient and structured communication.